2011
DOI: 10.1038/nsmb.2141
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the molecular evolution of SRP-GTPase activation by protein

Abstract: SIMIBI-class (named after the signal recognition particle, MinD, BioD) nucleotide-binding proteins appeared early in evolution 1 and contain GTPases, as well as ATPases, involved in the correct localization of cellular constituents. The MinD ATPase, as the central part of the Min system, regulates the determination of the cell division site in all bacterial species 2 . SRP-GTPases form a subfamily of the SIMIBI class, with only three members: the signal sequence-binding protein Ffh (SRP54 in Eukarya and Archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 49 publications
2
100
0
Order By: Relevance
“…In this study, we showed that purified full-length P. aeruginosa FlhF is a GTPase with a high K m (ϳ30 M), a low turnover rate (k cat ϭ 0.06/s), and a low V max (25 mol/h). These kinetic parameters are similar to those reported for another SRP-GTPase, B. subtilis FlhF (20 mol/h) (13).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this study, we showed that purified full-length P. aeruginosa FlhF is a GTPase with a high K m (ϳ30 M), a low turnover rate (k cat ϭ 0.06/s), and a low V max (25 mol/h). These kinetic parameters are similar to those reported for another SRP-GTPase, B. subtilis FlhF (20 mol/h) (13).…”
Section: Discussionsupporting
confidence: 75%
“…The FlhF proteins of Bacillus subtilis (BsFlhF) and C. jejuni (CjFlhF) were recently shown to have GTPase activity (13,14). However, the phenotypes associated with flhF deletion or mutation differ for these organisms and P. aeruginosa, making it difficult to generalize a role for FlhF in P. aeruginosa based on these studies.…”
mentioning
confidence: 80%
“…Proteins such as SRP68/72, SRP9/14, and SRP19 all contribute to the regulation of the pathway in ways that are not completely understood (reviewed in reference 3). It has been predicted that as-yet-unknown proteins may work in concert with the scRNA to regulate bacterial Ffh/FtsY activity (46,47). It appears that YlxM represents such an accessory factor.…”
Section: Discussionmentioning
confidence: 99%
“…YlxM may have a function analogous to that of YlxH, an accessory protein recently found to regulate the activity of FlhF, a protein involved in flagellar biosynthesis in B. subtilis (46). Like Ffh and FtsY, FlhF is a member of the SIMIBI family of GTPases.…”
Section: Discussionmentioning
confidence: 99%
“…FlhF is a GTPase protein and is similar to the signal recognition particle receptor FtsY (8,9). The GTPase motif of FlhF influences the intracellular location of this protein (10,11), and GTPase activity is stimulated through interactions with FlhG (12)(13)(14). FlhG is an ATPase protein and is similar to MinD, a cell division regulator in prokaryotes (15)(16)(17).…”
mentioning
confidence: 99%